2021
DOI: 10.1007/s11104-021-04853-9
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient stoichiometry of a plant-microbe-soil system in response to cover crop species and soil type

Abstract: Aims The theory of ecological stoichiometry mostly builds on studies of natural terrestrial ecosystems, whereas only limited stoichiometry information is available in response to agronomic practices. Methods We designed a greenhouse experiment in order to disentangle the specific role of cover crop identity and soil characteristic in affecting nutrient stoichiometry of a plant-microbe-soil system. Results Nutrient r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 91 publications
1
2
0
Order By: Relevance
“…Indeed, changes in plant communities can influence microorganism and enzyme activities [49,[112][113][114]. This finding is consistent with previous works showing that plant resources and their stoichiometry may strongly influence microbial traits [63,64,115,116]. Using soil enzyme vector analysis, Xiao et al [61] indicated that the microbial community was co-limited by C and P during secondary plant succession in a natural grassland.…”
Section: Microbial Resource Requirement Under the Different Cropssupporting
confidence: 78%
“…Indeed, changes in plant communities can influence microorganism and enzyme activities [49,[112][113][114]. This finding is consistent with previous works showing that plant resources and their stoichiometry may strongly influence microbial traits [63,64,115,116]. Using soil enzyme vector analysis, Xiao et al [61] indicated that the microbial community was co-limited by C and P during secondary plant succession in a natural grassland.…”
Section: Microbial Resource Requirement Under the Different Cropssupporting
confidence: 78%
“…The microbial stoichiometry supplies information about organic matter decomposition, patterns of nutrient limitation, and links between fluxes of C, N, and P (Philippot et al, 2013 ; Mouginot et al, 2014 ). Anyway, soil nutrient stoichiometry was recognized as the main predictor of bacterial and fungal diversity and composition even at a regional scale, being mainly driven by variation in soil C, N, and P resources, as affected by system management (Delgado-Baquerizo et al, 2017 ; Bragazza et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The element that limits the growth and reproduction of organisms can be inferred by ecological stoichiometric characteristics analysis. The organism can regulate its C:N:P ratio to accommodate variations in growth [129][130][131]. Therefore, when investigating the regulatory role of root exudates on soil nutrients, utilizing the variations in ecological stoichiometry characteristics to predict and quantify the feedback of soil nutrients on plant growth would be a simple and effective method.…”
Section: Application Of Ecological Stoichiometry In Psfmentioning
confidence: 99%